Cooperative liquidity and profitability in Brebes Regency - Nasiruddin Nasiruddin; Yenny Ernitawati; Anisa Sains Kharisma; Hilda Kumala Wulandari; Maftukhin Maftukhin (Enrichment : Journal of Management, 2023)
The purpose of this study was to analyze the health level of cooperatives in Brebes Regency. This study used a descriptive method with a purposive sampling method in selecting a sample of 36 cooperatives from 375 cooperatives in Brebes Regency. This study analyzes the aspects of liquidity and aspects of independence and growth. The results of this study from 36 samples that were used as research objects showed that in terms of liquidity only 1 cooperative was in the title of Liquid, namely KPRI Karib Sukses Mandiri. The other 2 cooperatives are under the title of Less Liquid, namely KJKS Al Muawanah and Kpri Prosperous. Other cooperatives are classified as illiquid. The independence and growth aspect is calculated using 3 ratios, namely the asset profitability ratio, the equity profitability ratio, and the operational independence ratio. There are 7 cooperatives whose asset profitability ratios are at a high level, namely above 10%, namely Kopkar Rukun Sejahtera at 12.31, Koppontren Shofwatussu'ada at 18.94, Kpri Harum at 10.99, Kpri Dwi Tunggal at 13.70, Kpri Families Prosperous at 14.40, Kpri SMEAN 1 Brebes was 13.70, Kpri SMPN I Brebes was 11.03. Of the 36 cooperatives, there are 2 cooperatives that have a profitability ratio of over 10%, namely Koppontren Shofwatussu'ada at 11.16 and Kpri Karib Sukses Mandiri at 11.44. Cooperatives that have an operational independence ratio above 150%, there are 5 cooperatives namely KJKS Al Muawanah with 146.99, Kopkar Rukun Sejahtera with 133.00, Kopontren Al Falah Mandiri with 100.00, Kopontren Al Hikmah with 116.61, Kpri Harum with 141.27.